Analisis Pengaruh Kepemimpinan Superleadership terhadap Kinerja dengan Komitmen sebagai Variabel Intervening - Hadi, Dwi Prasetyo (STIE Widya Manggala, 2011)
The objective of the research was to analyze a relation of Superleadership to the performance with intervening role of commitment (a case study at BKM Kabupaten Batang). Using a sampel of 167 employees at BKM Kabupaten Batang. Structural Equation Modelling (SEM) was used to analyze the variable. By using confidence level 95 % showed that superleadership and affective commitment had significant impact with p value 0,000; superleadership and Normative commitment had significant impact with p value 0,000; superleadership and Continuance commitment had significant impact withp value 0,000. By using statistical analysis showed that superleadership and performance had no significant impact with p value 0.068; Afective commitment and performance had no significant impact with p value 0.203; Normative commitment and performance had significant impact with p value 0.002 and Continuance commitment and performance had significant impact with p value 0.022.